Hubungan Fatigue dengan Kejadian Excessive Daytime Sleepiness pada Perawat - Septian Mixrova Sebayang; Dewi Astuti Pasaribu (Jurnal Riset Hesti Medan, 2021)
Nurses hold an important responsibility for maintaining patients’safety. It has been known that fatigue and sleepiness may result in errors with negative consequences for patient safety. The purpose of this study was to examine the relationship between fatigue and excessive daytime sleepiness among nurses. This research design is descriptive correlation. The total sample in this study was 36 nurses. This research was conducted at the Special Eye Hospital Medan. Sampling using purposive sampling. Data collection using the Three-Dimensional Work Fatigue Inventory (3D-WFI) and The Epworth Sleepiness Scale. Data analysis using the Chi-Square test. The results of this study indicate that the majority of nurses experience tired fatigue as many as 22 respondents (61.1%) compared to 14 respondents (38.9%) not tired. Chi Square test showed an association between fatigue and excessive daytime sleepiness (EDS) in nurses (P = 0.000 <α 0.05). This study recommends nurses to optimize the work hours of nurses to overcome daytime sleepiness, and for nurses to maintain conditions in order to avoid excessive sleepiness which can cause adverse event.